2011
DOI: 10.1007/s11670-011-0224-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of PDCD5 in peripheral blood serum of cancer patients

Abstract: Objective: Programmed cell death 5 (PDCD5) is an apoptosis related gene and plays an important role in the pathogenesis and development of cancer. Whether PDCD5 is present in peripheral blood serum has not been reported. The aim of this study is to determine the contents of PDCD5 protein in peripheral blood serum of cancer patients, as well as normal subjects.Methods: ELISA was used to detect the serum PDCD5 concentrations in 100 normal persons, 83 patients with breast cancer, 74 patients with gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…A strong correlation between PDCD5 and IL-17 levels in serum of RA patients has been determined in a previous study (25). Wang et al (13) found decreased expression of PDCD5 in peripheral blood of breast cancer, lung cancer and gastrointestinal cancer, however, the PDCD5 levels in cancer patients are not statistically different from that of normal persons. The level of PDCD5 in serum may be used as a novel marker for HCC.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A strong correlation between PDCD5 and IL-17 levels in serum of RA patients has been determined in a previous study (25). Wang et al (13) found decreased expression of PDCD5 in peripheral blood of breast cancer, lung cancer and gastrointestinal cancer, however, the PDCD5 levels in cancer patients are not statistically different from that of normal persons. The level of PDCD5 in serum may be used as a novel marker for HCC.…”
Section: Discussionmentioning
confidence: 97%
“…Wang et al (12) illustrated a significant elevation of PDCD5 concentrations in both plasma and synovial fluid of knee rheumatoid arthritis (RA) patients compared to osteoarthritis (OA) patients and the control plasma concentrations. The serum PDCD5 levels in breast cancer, gastrointestinal tract cancer and lung cancer patients were separately compared with healthy persons by Wang et al (13). However, the significance of serum PDCD5 and its changes in various cancers await further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was reported that PDCD5 also regulates autophagy to protect against cardiac remodeling (12). Dysregulation of PDCD5 has been found to be involved in different type of tumors (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The antitumor activity of PDCD5 has been also proposed (23)(24)(25)(26)(27)(28)(29) and low expression level of PDCD5 has been suggested to be a prognostic indicator for cancers (30).…”
Section: Introductionmentioning
confidence: 99%
“…PDCD5 is an apoptosis-related gene cloned from TF-1 cells undergoing cytokine deprivation-induced apoptosis (3). In a study by Wang et al (12), no statistically significant difference was observed between the serum PDCD5 concentrations in healthy patients and the patients with breast cancer, gastrointestinal cancer or lung cancer. In this study, it was demonstrated that preoperative serum levels of PDCD5 protein in the patients with HCC were significantly lower than the postoperative serum levels.…”
Section: Discussionmentioning
confidence: 99%